A Prospective Comparison of Bipolar I and II Subjects With and Without Comorbid Alcohol Dependence From the COGA Dataset - Preuss, Ulrich W.; Hesselbrock, M. N.; Hesselbrock, V. M. (Frontiers in Psychiatry, 2020)
Objective: Comorbidity of alcohol use disorders in bipolar subjects is high as indicated by epidemiological and clinical studies. Though a more severe course of bipolar disorder in subjects with comorbid alcohol dependence has been reported, fewer studies considered the longitudinal course of alcohol dependence in bipolar subjects and the prospective course of comorbid bipolar II subjects. Beside baseline analysis, longitudinal data of the COGA (Collaborative Study on Genetics in Alcoholism) were used to evaluate the course of bipolar I and II disordered subjects with and without comorbid alcohol dependence over more than 5 years of follow-up. Methods: Characteristics of bipolar disorder, alcohol dependence and comorbid psychiatric disorders were assessed using semi-structured interviews (SSAGA) at baseline and at a 5-year follow-up. Two hundred twenty-eight bipolar I and II patients were subdivided into groups with and without comorbid alcohol dependence. Results: Of the 152 bipolar I and 76 bipolar II patients, 172 (75, 4%) had a comorbid diagnosis of alcohol dependence. Bipolar I patients with alcohol dependence, in particular women, had a more severe course of bipolar disorder, worse social functioning and more suicidal behavior than all other groups of subjects during the 5-year follow-up. In contrast, alcohol dependence improved significantly in both comorbid bipolar I and II individuals during this time. Conclusions: A 5-year prospective evaluation of bipolar patients with and without alcohol dependence confirmed previous investigations suggesting a more severe course of bipolar disorder in comorbid bipolar I individuals, whereas bipolar II individuals were less severely impaired by comorbid alcohol use disorder. While severity of alcohol dependence improved during this time in comorbid alcohol-dependent bipolar I patients, the unfavorable outcome for these individuals might be due to the higher comorbidity with personality and other substance use disorders which, together with alcohol dependence, eventually lead to poorer symptomatic and functional clinical outcomes.